Deteksi mikrofilaria Brugia malayi pada nyamuk Mansonia spp dengan pembedahan dan metode PCR di Kabupaten Tanjung Jabung Timu - Santoso Santoso; Yahya Yahya; Nungki Hapsari Suryaningtyas; Katarina Sri Rahayu (Loka Litbang Kesehatan Pangandaran, 2015)
Filariasis is a public health problem in East Tanjung Jabung. Eventhough that mass treatment had been carried out since 2002, there were still villages with microfilaria rate >1%. This study aims to detect filarial worm larvae in the mosquitoes with dissections and PCR method. The mosquitoes used in this study were Mansonia spp. The number of mosquitoes that examined was 450,133 and some of Mansonia mosquitoes were checked by PCR. The result showed that microscopic dissection did not found stage 3 (L3) of filarial worm larvae in the mosquitoes. The results from PCR test showed the presence of B. malayi DNA in 8 samples of Ma. indiana. Mansonia indiana is a potential vectors for Brugia malayi filariasis in East Tanjung Jabung. PCR method is more sensitive examination in detecting microfilaria compared with dissection method.